HIV/HBV COINFECTION: ASSOCIATED FACTORS WITH HBV FUNCTIONAL CURE - Teixeira Amorim, Laila Maria (2025)
HIV research has remained frequent since its discovery. HIV/HBV co-infection is highly significant as it impacts on the natural history of chronic HBV infection, increasing morbidity and mortality. Objective: To identify the prevalence of functional cure in patients with HIV/HBV coinfection and the possible factors associated with this cure. Method: This is a retrospective cohort study conducted between July 2023 and August 2024 in two healthcare centers in Fortaleza. Results: Of the 175 coinfected patients included in the study, only 146 had access to control HBsAg. In the comparative analysis between the two groups, factors such as the absence of positive HBeAg and lack of detection of HBV-DNA were statistically significant for HBsAg clearance. Conclusion: These results suggest that proper control of HBV, particularly in patients with negative HBeAg, is associated with a higher prevalence of functional cure.